Effect of an educational training intervention on rapid tranquillisation usage – a pilot nursing study in a public hospital in Singapore. (June 2019) - Balasundaram, Bharathi; Loh, Soak Yee; Nadkarni, Pallavi; Jiang, Li Na; Jayaram, Mahesh; Kam, Jia Wen; Yap, Hwa Ling; Shashu Ayengar, Krishnasamy; Bai, Jing Yuan
Background: Studies evaluating nursing educational initiatives in rapid tranquillisation procedures are lacking. Objective: This pilot study in a public hospital in Singapore evaluated the effect of an educational training intervention on knowledge and confidence of nurses using rapid tranquillisation in two medical wards. Method: The study design was a pilot pre- and post-test single-group design on a voluntary sample of 75 nurses. The educational training intervention comprised of a 60 min interactive presentation followed by a small-group-based case discussion conducted by an advanced nurse practitioner. Knowledge was measured using a 'test the knowledge' questionnaire; a Likert scale measured perceived level of confidence. Results: The knowledge score (overall score = 11) was significantly improved from pre-training (average score: 5.1 (standard deviation, 1.3)) to post-training (average score: 8.1 (standard deviation, 1.8)), t = −12.61, p < 0.001. The participants were more confident after training ( p < 0.001). Conclusion: This study has shown that a classroom training intervention of nurses in rapid tranquillisation procedures improved knowledge and confidence in dealing with patient violence in hospitals and added to the safe practice of rapid tranquillisation. Further studies evaluating the long-term and clinical impact of training with more rigorous study designs are needed to replicate these promising findings.